Orchestral masterpieces under the microscope - Del Mar, Jonathan 1951- (The Boydell Press, 2023)
How does a conductor know whether the score they use is what the composer wrote? How do orchestral players know that their parts are reliable and reflect the latest scholarship? As Jonathan Del Mar reminds us in this ground-breaking book, editions of the orchestral repertoire are beset by textual problems: simple misprints, mistakes in the score or player's part, or hopelessly outdated scores at odds with current scholarship
Also issued in print: 2023. - Includes bibliographical references
Keywords: Strauss, Richard -- 1864-1949 -- Ein Heldenleben; Wagner, Richard -- 1813-1883 -- Die Meistersinger von Nürnberg; Strauss, Richard -- 1864-1949 -- Konzerte -- TrV 292; Strauss, Richard -- 1864-1949 -- Konzerte -- TrV 117; Weber, Carl Maria von -- 1786-1826 -- Ouvertüre zum Beherrscher der Geister; Strauss, Richard -- 1864-1949 -- Metamorphosen; Score reading and playing; Errata; Composition (Music); Orchestermusik; Präludium; Edition; Komposition -- Musik; Quellenkritik; Verzeichnis